ANALISIS EFESIENSI USAHA DAN STRATEGI PEMASARAN HOME INDUSTRY KERUPUK UBI DI DESA NANGAI AMEN KECAMATAN LEBONG UTARA - Hidayahtul Fitriah; Irnad Irnad; Reswita Reswita (Jurnal Inovasi Penelitian, 2022)
The home industry is one of the places where people are able to grow and develop independently by providing a large increase and a strategic role in increasing family income. In addition, home industry is also a business activity that is able to provide broad economic services to the community, and can play a role in increasing family income, reducing unemployment and improving community welfare. This research was conducted in Nangai Amen Village, North Lebong District. This study aims to analyze the efficiency of the home industry of sweet potato crackers and develop strategic priorities for the development of a home industry of sweet potato crackers in Nangai Amen Village, North Lebong District. The data analysis method used in this research is business efficiency analysis using Revenue Cost Ratio (R/C). Meanwhile, to determine the priority of business development strategy using the method of Analytical Hierarchy Process (AHP). AHP analysis is used to analyze the strategic priorities of the home industry of sweet potato crackers which include product, promotion, price and place. The results showed that the average income received by the home industry was Rp.1.202.688/month. Based on the R/C analysis, the value was 1,8. It can be concluded that the home industry of sweet potato crackers in Nangai Amen Village deserves to be continued. The development priorities of the sweet potato cracker home industry from the results of this study are:(1) product subsystem, namely improving product quality with an alternative weight of 0.562.(2) the promotion subsystem, namely the expansion of marketing reach with an alternative weight of 0.487.(3) the price of the subsystem utilizes the development of BUMDES with an alternative weight of 0.535.(4) the place of the subsystem, namely utilizing the village to improve facilities and infrastructure with an alternative weight of 0.347.